THE LEGAL STATUS OF WILL EXECUTORS IN DEEDS OF BEQUEST UNDER PMNA/KBPN NO. 3 OF 1997 AND ARTICLE 1813 OF THE CIVIL CODE - Deas Oktaviara Habiansyah; Riana Susmayanti; Endang Sri Kawuryan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research aims to analyze the legal status of the executor of a will (executeur testamentair) in the deed of gift by will (hibah karena wasiat) as regulated in Article 112 paragraph (1) a point 3 letter b of the Regulation of the State Minister for Agrarian Affairs/Head of the National Land Agency No. 3 of 1997 in relation to Article 1813 of the Indonesian Civil Code. The main issue lies in the normative conflict between the concept of a power of attorney, which terminates upon the death of the grantor, and the executor’s legal mandate, which remains valid after the testator’s death. This study employs a normative legal research method using statutory and conceptual approaches, grounded in the theories of legal certainty proposed by Gustav Radbruch, Van Apeldoorn, and Hans Kelsen. The findings indicate that the executor of a will has a distinct legal position from an ordinary agent, as their authority derives from a legal mandate rather than a contractual relationship. Therefore, the executor’s authority does not terminate upon the testator’s death, provided that it is carried out in accordance with the will and applicable law. Nevertheless, normative ambiguity persists, leading to interpretative discrepancies among notaries and land deed officials (PPAT). Regulatory clarification is required to strengthen the executor’s legal legitimacy and ensure the implementation of the testator’s final will in line with the principles of legal certainty and justice.